﻿Graded levels of dietary pink oyster mushroom, Pleurotus djamor meal, affect growth, feed efficiency, lipase activity, and fiber content in final whole body of fingerlings of the Nile tilapia, Oreochromis niloticus (Actinopterygii: Cichliformes: Cichlidae) - Mario Eduardo Sosa; Silvia Cappello-García; Rafael Martínez-García; Susana Camarillo-Coop; Rocío Guerrero-Zarate; Otilio Méndez-Marín; Carlos Alfonso Álvarez-Gonzaléz; Uriel Rodríguez-Estrada (Acta Ichthyologica et Piscatoria, 2023)
The presently reported study was aimed to determine the effects of graded levels of dietary pink oyster mushroom (Pleurotus djamor) meal (POMM), in growth, feed efficiency, protein utilization, digestive enzymes activities, and whole-body proximate composition of Nile tilapia, Oreochromis niloticus (Linnaeus, 1758), fingerlings (0.3 ± 0.01 g). The experimental design included a control diet (POMM0) formulated with soybean meal, as the main protein source, and four diets designed with increasing levels of POMM: 25% (POMM25); 50% (POMM50); 75% (POMM75); and 100% (POMM100). Experimental diets were administered to 420 fish, randomly distributed in 15, 100-L tanks. The feeding experiment lasted 45 days. Diets and the final whole body were submitted to a proximate composition analysis. Growth, feed efficiency, protein utilization, and digestive enzyme activities were assessed. Compared to POMM0 and POMM25, weight gain (WG), and specific growth rate (SGR), significantly (P < 0.05) decreased in fish that were fed POMM50, POMM75, and POMM100%. Feed conversion ratio (FCR), protein efficiency ratio (PER), and survival rate (SR) were not significantly affected by experimental diets. Daily feed intake (DFI), and daily protein intake (DPI), decreased as POMM increased in diets. Compared to POMM0 experimental group, condition factor (K), showed a significantly higher value in fish that were fed POMM50, and POMM100 experimental diets. Crude fiber of the final whole body of POMM100 resulted in significantly higher (P < 0.05) compared to that shown in fish fed the rest of the experimental diets. Acid and alkaline proteases, trypsin, chymotrypsin, leucine aminopeptidase, and amylase of Nile tilapia fingerlings, were not significantly affected by experimental diets. Compared to fish fed POMM0 and POMM25 diets, experimental fish fed POMM50, POMM75, and POMM100 showed a reduction in lipase activity. In conclusion, a POMM level higher than 25% affects growth and lipase activity. While a POMM level higher than 50% affects fiber content in a whole body of the final fish.